2022
DOI: 10.3390/su14052505
|View full text |Cite
|
Sign up to set email alerts
|

Effective Sustainability Messages Triggering Consumer Emotion and Action: An Application of the Social Cognitive Theory and the Dual-Process Model

Abstract: Communication utilizing proper message framing is a crucial component in the promotion of sustainability and other related activities. Additionally, engaging all stakeholders in sustainable communication and endeavors is proven to be essential to corporate success. This is especially true for textile and apparel retailers, as they strive to gain competitive advantages through the incorporation of sustainability in their communication with their stakeholders. Therefore, promotional activities consisting of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…In addition, social cognitive theory has opened up a new path for social learning process (Scott et al, 2022). Employees bear some negative impacts (e.g., knowledge hiding behavior) from the antecedent of differential leadership management through a series of psychological dynamics caused by a person's information-processing system, which consists of five dimensions, including coding, explanation, search response, reaction evaluation, and reaction practice (Rakib et al, 2022). Hence, exploring a new insight into the link between differentiated management and knowledge hiding is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, social cognitive theory has opened up a new path for social learning process (Scott et al, 2022). Employees bear some negative impacts (e.g., knowledge hiding behavior) from the antecedent of differential leadership management through a series of psychological dynamics caused by a person's information-processing system, which consists of five dimensions, including coding, explanation, search response, reaction evaluation, and reaction practice (Rakib et al, 2022). Hence, exploring a new insight into the link between differentiated management and knowledge hiding is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In social cognitive theory, triadic reciprocal causation is used to interpret psychosocial functioning. According to triadic reciprocal causation, behavioral, cognitive and other personal and environmental factors are the determinants of mutual influence ( Wood and Bandura, 1989 ; Rakib et al, 2022 ). Entrepreneurial behavior is affected by cognitive and personal factors, such as entrepreneurial self-efficacy and personal capabilities ( Bandura, 1977 ; Leybourne and Sadler-Smith, 2006 ; Antoncic et al, 2015 ; Schunk and DiBenedetto, 2020 ; Cai et al, 2020b ).…”
Section: Theoretical Background and Conceptual Modelmentioning
confidence: 99%
“…In light of the entrepreneurial event model, entrepreneurial self-efficacy is a prerequisite for entrepreneurial intention and behavior ( Esfandiar et al, 2019 ; Cai et al, 2020b ; Antoncic et al, 2021 ; Rakib et al, 2022 ). The entrepreneurial event model posits that perceptions of feasibility are directly influenced by self-efficacy.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we also examined the potential mediating role of emotional arousal (positive vs. negative), which is one of the key determinants of pro-environmental behaviors [ 19 ]. Although the influence of emotions has been overlooked within environmental research for a long time, recent studies have identified affective motives as important factors in affecting sustainable behaviors [ 20 , 21 ]. For instance, the literature indicates that emotions exert a crucial impact on rational processes [ 22 ] and may motivate environmental protection even more than data-intensive arguments [ 23 ].…”
Section: Introductionmentioning
confidence: 99%